Biogeographical structure and endemism pattern in reptiles of the Western Palearctic. (April 2018) - Ficetola, Gentile Francesco; Falaschi, Mattia; Bonardi, Anna; Padoa-Schioppa, Emilio; Sindaco, Roberto
The analysis of biogeographical structure and patterns of endemism are central topics of biogeography, but require exhaustive distribution data. A lack of accurate broad-scale information on the distribution of reptiles has so far limited the analyses of biogeographical structure. Here we analysed the distribution of reptiles within the broad-sense Western Palearctic to assess biogeographical regionalization using phylogenetic and non-phylogenetic approaches, identified areas of endemism and evaluated the environmental factors promoting community uniqueness and endemism. We gathered distributional records from the literature and from the field, mapping the distribution of all the Western Palearctic reptiles on a 1-degree resolution grid. βsim dissimilarity and hierarchical clustering was used to identify bioregions, analysing data both at the species and at the genus level, and considering phylogenetic dissimilarity. Consensus areas of endemism were identified on the basis of the optimality criterion. We then assessed whether biogeographical structure is related to present-day climate, insularity, orography and velocity of climate change during the Late Quaternary. The genus-level analysis identified five main biogeographical regions within the Western Palearctic, in partial agreement with previous proposals, while the species-level analysis identified more bioregions, largely by dividing the ones identified by genera. Phylogenetic bioregions were generally consistent with the non-phylogenetic ones. The strongest community uniqueness was observed in subtropical warm climates with seasonal precipitation and low productivity. We found nine consensus areas of endemism, mostly in regions with limited velocity of Quaternary climate change and warm subtropical climates. The biogeographical structure of Western Palearctic reptiles is comparable to what has been observed in other vertebrates, with a clear distinction between the Saharo-Arabian-Sindian and Euro-Mediterranean herpetofaunas. Unlike other vertebrates, in reptiles the highest uniqueness and endemism is observed in dry climates, but the velocity of climate change during the Quaternary remains a major driver of endemism across all the vertebrates.